Tackling Over-Schooling and Employability Challenges of Nigerian Graduates for National Development - Akintunde, Oluyomi O.; Ugboha, Grace (NIU Journal of Social Sciences; Vol 6 No 1 (2020): KIU Journal of Social Sciences, Vol. 6 No. 1, March 2020, 2020)
Over-schooling and un-employability challenges bedevil graduates in Nigeria. Over-schooling breeds low productivity, job dissatisfaction, lack of motivation, poor human relations, violence and frustration. These portend danger for national development. This paper focuses on how to tackle over-schooling and un-employability in order to minimize the negative effects. The techniques proposed include acquisition of job creation and employability skills; sensitization of graduating class; overhauling of SIWES program and utilization of technology facilities for improved employability of graduates. When over-schooling and employability challenges of graduates are curtailed, there will be production of work-ready graduates and entrepreneurs; increased productivity and enhanced national development. Keywords: Over-schooling, employability, challenges, Nigerian graduates, national development, tackling.